A solution for nosocomial infection in healthcare facilities - Parsia, Yasaman; Puteri Fadzline, Muhamad Tamyez (Institute of Medico-Legal Publications, 2019)
Cross-infections in healthcare facilities, collectively known as Nosocomial Infection (NI), remain a global issue. Numerous people in Healthcare facilities (HFs) die all the time due to the spread of such diseases, specially NIs. Governmental HFs are burdened with increased expenses as a result of the unchecked transmission of cross-infections across their departments. This conceptual paper, firstly, attempts to present the severity of NI prevalence and propose a hypothesis in discussions of the role of HF layouts in controlling such cross-infections. Lastly, it focuses on the comprehension for controlling of the risks of cross-infections transiting between HF departments and facilities.